Green Solvents for Lipid Extraction From Microalgae to Produce Biodiesel - Liu, Xiaofang; Yu, Dayong; Luo, Hangyu; Li, Can (Frontiers in Chemistry, 2022)
Microalgae have been considered as the third generation feedstock for biodiesel production and lipid extraction plays a significant role inefficient production of biofuels. Numerous technologies including chemical, mechanical, biological are provided but the high efficiency and have potential to be applied on an industrial scale are demanded. This review discusses the factors that influence biodiesel quality and the relative green and sustainable solvents for lipid extraction.